2021
DOI: 10.1364/optica.425290
|View full text |Cite
|
Sign up to set email alerts
|

Tunable unidirectional surface plasmon polaritons at the interface between gyrotropic and isotropic conductors

Abstract: Unidirectionally propagated electromagnetic waves are rare in nature but heavily sought after due to their potential applications in backscatter-free optical information processing setups. It was theoretically shown that the distinct bulk optical band topologies of a gyrotropic metal and an isotropic metal can enable topologically protected unidirectional surface plasmon polaritons (SPPs) at their interface. Here, we experimentally identify such interfacial modes at terahertz frequencies. Launching the interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The THG output from the final sample (red square dot) is 75 times stronger than the as-grown film, while our simulation predicts an enhancement twice as large (red solid curve). Such difference is likely caused by the nonideal surface quality of the Au film, which is known to produce degraded optical responses as compared to the bulk. , Figure d summarizes the THG conversion efficiencies obtained using different substrate/capping layer designs. Using a simple film stack with an only 13 nm thick NLO medium, an efficiency of nearly 0.01% is achieved in a single reflection, rivaling the performance of nonlinear metasurface structures that involve far more complex device fabrications.…”
Section: Resultsmentioning
confidence: 99%
“…The THG output from the final sample (red square dot) is 75 times stronger than the as-grown film, while our simulation predicts an enhancement twice as large (red solid curve). Such difference is likely caused by the nonideal surface quality of the Au film, which is known to produce degraded optical responses as compared to the bulk. , Figure d summarizes the THG conversion efficiencies obtained using different substrate/capping layer designs. Using a simple film stack with an only 13 nm thick NLO medium, an efficiency of nearly 0.01% is achieved in a single reflection, rivaling the performance of nonlinear metasurface structures that involve far more complex device fabrications.…”
Section: Resultsmentioning
confidence: 99%
“…The nonlocal parameter can be used as an additional dimension to elucidate the topological phase transitions when the nonlocal effect is considered in the chiral media system. The nonlocal effect in metamaterial means that the dielectric function is not only frequency dependent but also spatial dispersive [41,56,57]. In the absence of the nonlocal effect, the bulk plasma mode ω = ω p is non-dispersion along the z axis.…”
Section: Type I/ii Weyl Points and Topological Phase Transitionsmentioning
confidence: 99%
“…These unidirectional SPPs, known as unidirectional surface magnetoplasmons (USMPs) for several decades, have recently regained interest in the context of topological electromagnetics 7 15 . It has been revealed that true USMPs are topologically protected 12 , 13 and thus robust against nonlocal effects. These USMPs can be immune to backscattering at disorders due to the absence of a back-propagating mode in the system.…”
Section: Introductionmentioning
confidence: 99%